Use of digital media for the education of health professionals in the treatment of childhood asthma - Helena F. Velasco; Catiane Z. Cabral; Paula P. Pinheiro; Rita de Cassia S. Azambuja; Luciano S. Vitola; Márcia Rosa da Costa; Sérgio L. Amantéa (Elsevier, 2015)
OBJECTIVES: Inhalation therapy is the main treatment for asthma and its adequate use has been a factor responsible for disease control; therefore, the aim of the study was to determine whether a digital media tool, which features portability on mobile phones, modifies the assimilation of the inhalation technique. METHODS: A total of 66 professionals working in the health care area with the pediatric population were selected. They were submitted to a pre-test on their knowledge of inhalation therapy. The professionals were randomized into two groups (A and B). Group A received a media application on their mobile phones showing the steps of inhalation therapy, while group B received the same information in written form only. A post-test was applied after 15 days. The results (pre- and post-) were analyzed by two pediatric pulmonologists. RESULTS: Of the 66 professionals, 87.9% were females. Of a total possible score of ten, the mean score obtained in the pre-test was 5.3 ± 3, and in the second test, 7.5 ± 2 (p < 0.000). There were no significant differences when comparing the two groups (p = 0.726). The nurses had the lowest mean scores in the initial test (2.3 ± 2); however, they were the group that learned the most with the intervention, showing similar means to those of other groups in the second test (6.1 ± 3). CONCLUSION: There was significant improvement in knowledge about inhalation therapy in all professional categories using both methods, demonstrating that education, when available to professionals, positively modifies medical practice.